Argumentation Skills of Pre-Service Elementary Teachers on Atmospheric Pressure - Pelin Mete (Journal of Science Learning, 2023)
In the present study, atmospheric pressure, an abstract concept that learners generally have difficulty understanding and explaining, was presented to pre-service elementary teachers (PSTs) with the method of argumentation. The argument levels of the PSTs were examined using the Predict - Observe - Explain (POE) experiments in teaching the subject of "atmospheric pressure."   The study includes both the development of the worksheets and the application of the developed worksheets. The researcher developed four POE worksheets and used them in two ways. First, PSTs did two POE experiments in the science lab to learn by doing atmospheric pressure. Second, PSTs watched two videos about atmospheric pressure. Data collection tools consist of POE worksheets and in-class discussion records made during the implementation. The worksheet analysis prepared an argumentation rubric according to the Toulmin argument level. Descriptive analysis was performed on the worksheets according to the argumentation rubric, and the change and development of the PSTs' argument skills were evaluated. Although, as a result of the study, the PSTs had difficulty forming arguments at the beginning, as the practice progressed, their argument-forming skills improved, and the argument levels of the PSTs were moved to higher levels. However, it was noted that the PSTs' level of high-level argument formation was limited. In contrast, most of the PSTs in the experiments made only one claim and had difficulties justifying it.